Dinâmica dos processos de coluvionamento no semiárido de Alagoas - Maciços De Água Branca e Mata Grande - Silva, Adelaine Firmino da (2025)
The main objective of this research was to verify the depositional dynamics of colluvial deposits in a modeled colluvial slope/colluvium ramp containing a diversity of lithologies between mud and gravel in a semi-arid climate regime. Specifically, it was sought: a) to determine the macro geomorphological context of occurrence of slope deposits with potential for procedural analysis contained in the study area; b) to correlate macrofacies with microfacies; c) to infer the properties of depositional agents of colluvial units according to their facies; d) to provide classification of colluvial units in the rheological and fluid mechanics perspective; e) to verify if there are different macro and microsedimentological signatures for colluvial units between depositional sectors - proximal to distal; and f) determine the paleoenvironmental significance of colluvial units. The methodology integrated office work, field, and laboratory procedures. During the office stage, geomorphological modeled and surfaces were identified and compartmentalized. In the field, a survey of substrates and surface formations in the study area was carried out; among these, 34 outcrops of colluvial deposits were identified in a modeled colluvial slope/colluvial ramp formation. Three outcrops were selected from the distal, medial, and proximal sectors with greater potential for describing their records. Analyses were performed at macro- and micro-sedimentological scales, as well as Optically Stimulated Luminescence (OSL) dating. The mapping of the macro-geomorphology of the area allowed the spatial identification of the following modeled and geomorphic surfaces: Southern Sertanejas Depression, its respective morphostructural units (Pediplain and Massif), and modeled (summits, residual relief,slope with colluvial cover, inselberg, eluvium-covered slope, dissected pediments I and II, and alluvial plain). Regarding the stratigraphy of the colluvial deposits, similar facies were identified in the distal, medial, and proximal sectors: Laminated sandy mud (massive in the field), massive gravelly mud, and massive muddy gravel. The cross analysis of the data revealed that over the last 15.000 years BP, the landscape has been subjected to repeated episodes of slope instability, associated with paleoclimatic fluctuations. Finally, the combination of macro- and microsendimentological criteria enabled the identification of the flows responsible for the deposit formation (end member) and the understanding of mechanisms linked to depositional dynamics.